In Pursuit of Excellence: Student-Athlete Achievers’ Motivations, Opportunities, and Struggles - Santillan, Nanette L.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
Twenty-first-century education recognizes the role of sports as one framework for life-long skills, values, health, and well-being. The purpose of the study was to explore the on and off-field experiences of the six Junior High School student-athletes, the driving forces associated with their participation, and its influences and contribution to their excellent performance both in academics and in sports. This study utilized the qualitative research design using the phenomenological approach to gather insights into the lived experiences of the participants. The recursive textual data analysis revealed five core themes and the essence of the phenomenon: Motivated to Excel, Strong Support System, Rewarding Opportunities, Surpassed the Hurdles, and Exercised Self-Regulation. The themes revealed that the participants highly valued the positive impact of their sports involvement and the support of significant persons in their life. The findings implied that a comprehensive understanding of the intrinsic and extrinsic motivations of the student-athletes, their self-regulation skill, and support system facilitated a more effective approach in providing a nurturing learning environment that enhances academic performance, sports skills, and holistic health.